Environmental Origin of the Genus Bordetella - Hamidou Soumana, Illiassou; Linz, Bodo; Harvill, Eric T. (Frontiers in Microbiology, 2017)
Members of the genus Bordetella include human and animal pathogens that cause a variety of respiratory infections, including whooping cough in humans. Despite the long known ability to switch between a within-animal and an extra-host lifestyle under laboratory growth conditions, no extra-host niches of pathogenic Bordetella species have been defined. To better understand the distribution of Bordetella species in the environment, we probed the NCBI nucleotide database with the 16S ribosomal RNA (16S rRNA) gene sequence from pathogenic Bordetella species. Bacteria of the genus Bordetella were frequently found in soil, water, sediment and plants. Phylogenetic analyses of their 16S rRNA gene sequences showed that Bordetella recovered from environmental samples are evolutionarily ancestral to animal-associated species. Sequences from environmental samples had a significantly higher genetic diversity, were located closer to the root of the phylogenetic tree and were present in all ten identified sequence clades, while only four sequence clades possessed animal-associated species. The pathogenic bordetellae appear to have evolved from ancestors in soil and/or water and we show that, despite being animal-adapted pathogens, Bordetella bronchiseptica and Bordetella hinzii have preserved the ability to grow and proliferate in soil. Our data implicate soil as a probable environmental origin of Bordetella species, including the animal-pathogenic lineages. Soil may further constitute an environmental niche, allowing for persistence and dissemination of the bacterial pathogens. Spread of pathogenic bordetellae from an environmental reservoir such as soil may potentially explain their wide distribution as well as frequent disease outbreaks that start without an obvious infectious source.